Harmonizing Traditional and Modern Maternal Healthcare Practices in Cirebon, Indonesia - Busro, Busro; Hilmi, Fuad; Qodim, Husnul (Journal of Education Culture and Society, 2024)
Aim. This research aims to explore the integration of Traditional Knowledge and Traditional Practices during pregnancy and childbirth with Modern Health Knowledge and Practices in Cirebon, Indonesia,Methods. This research uses a qualitative method that includes participatory observation and interviews. Participants in this study consisted of pregnant mothers or patients giving birth in village health centres in Cirebon. Data was collected through participatory observations during visits to health centres and in-depth interviews with the participants.Results. The research results indicate that this integration occurs naturally in Cirebon. Respondents combine traditional and modern healthcare practices to meet their health needs during pregnancy and childbirth, taking into consideration cultural factors, religion, family support, healthcare accessibility, and past experiences.Conclusion. This study demonstrates that the integration of Traditional Knowledge and Traditional Practices during pregnancy and childbirth with Modern Health Knowledge and Practices is crucial in maternal healthcare practices in Cirebon, Indonesia.Cognitive value. The findings of this study can assist healthcare practitioners in improving the quality of maternal healthcare services in Indonesia and can serve as a reference for future research.